Optimization of microwave assisted process for extraction of nutmeg seed essential oil - SAFEENA P. A SRAVAN RAJ SREELATHA E STENY SIMON THEERTHA M. S; Dr. Prince M. V (Guide) (Tavanur 2017 Kelappaji College of Agricultural Engineering and Technology)
Optimization of microwave assisted process for extraction of nutmeg seed essential oil
Optimization of microwave assisted process for extraction of nutmeg seed essential oil